Wine : a social and cultural history of the drink that changed our lives. - Phillips, Roderick (Infinite Ideas classic wine library., 2018)
Wine looks at how wine has been used to demarcate social groups and genders, how wine has shaped facets of social life as diverse as medicine, religion, and military activity, how vineyards have transformed landscapes, and how successive innovations in wine packaging have affected and been affected by commerce and consumption.